Solidaritas Sosial Pedagang Kaki Lima terhadap Tingkah Laku Konsumen di D.I Yogyakarta - Hendra, Djaja (POPULIKA, 2019)
The presence of street vendors in Indonesia sometimes quiet disturbing especially for pedestrian and the motorist. However, they are also needed by the housewives to buy to rather than going to the market, supermarket or mall just to buy few things or only for a walk. Usually the street vendors had actually had place by the policy of the local government, however, maybe because of the little people know or with some other reason, the available places sometimes are left unused. The research is done towards 20 respondents with qualitative study. The method used is the phenomethologist.Â  The result of the research gotten are as follow: First, most of the respondents come from Tegal city, approaching another big cities in Java, second, most of the local citizens search for additional income from that place; third, generally the things prepared are fast food; generally the sellers from outside of the region go with their own vehicle and using pushed carriage for the local citizen.